2012
DOI: 10.1093/protein/gzs072
|View full text |Cite
|
Sign up to set email alerts
|

Advanced evolutionary molecular engineering to produce thermostable cellulase by using a small but efficient library

Abstract: We aimed at constructing thermostable cellulase variants of cellobiohydrolase II, derived from the mesophilic fungus Phanerochaete chrysosporium, by using an advanced evolutionary molecular engineering method. By aligning the amino acid sequences of the catalytic domains of five thermophilic fungal CBH2 and PcCBH2 proteins, we identified 45 positions where the PcCBH2 genes differ from the consensus sequence of two to five thermophilic fungal CBH2s. PcCBH2 variants with the consensus mutations were obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Mutagenesis work performed on PcCel6A revealed several properties of noncatalytic residues of this enzyme (see Heinzelman et al, 2009;Ito et al, 2013;Tachioka et al, 2016). In our recent work, the substitution mutation W267C was found to be a critical mutation for the degradation of crystalline cellulose III I but not of amorphous phosphoric acid-swollen cellulose (Tachioka et al, 2016), which was a similar finding to the work on TrCel6A (Koivula et al, 1998).…”
Section: Noncatalytic But Notable Residues Of Pccel6asupporting
confidence: 79%
See 2 more Smart Citations
“…Mutagenesis work performed on PcCel6A revealed several properties of noncatalytic residues of this enzyme (see Heinzelman et al, 2009;Ito et al, 2013;Tachioka et al, 2016). In our recent work, the substitution mutation W267C was found to be a critical mutation for the degradation of crystalline cellulose III I but not of amorphous phosphoric acid-swollen cellulose (Tachioka et al, 2016), which was a similar finding to the work on TrCel6A (Koivula et al, 1998).…”
Section: Noncatalytic But Notable Residues Of Pccel6asupporting
confidence: 79%
“…In a previous study, we cloned and recombinantly expressed PcCel6A and found that the hydrolysis rate of PcCel6A was greatly accelerated by a polymorphic change of crystalline cellulose (Igarashi et al, 2012). PcCel6A has been the target of protein engineering aimed at improving its thermostability (Heinzelman et al, 2009;Ito et al, 2013), and we have also recently applied random mutagenesis to this enzyme (Tachioka et al, 2016). Here, we report the structure of the CD of PcCel6A in its apo form and in complex with the ligand cellobiose.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The best variant showed 9.1°C increase in the mid-point of thermal denaturation and contained eight consensus mutations. In a similar study, five thermophilic proteins were aligned to predict 41 consensus mutations in the catalytic domain of cellobiohydrolase II from Phanerochaete chrysosporium [37]. After the first round of screening, 13 advantageous single and double mutations were identified which were randomly recombined and screened to identify a variant with significantly increased thermostability.…”
Section: Stochastic Approachesmentioning
confidence: 99%
“…Large-scale domain mixing experiments will be conducted to determine best combinations of CBM, linker and GH family members [80][81][82][83][84]. These experiments will not only provide important information on the relationship between structure and activity, but also provide new, high activity cellulases to reduce the cost of producing biofuels.…”
Section: Celmentioning
confidence: 99%